2018
DOI: 10.3389/fpsyg.2018.00878
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure Schedule Effects on Generalization of Taste Aversion and Palatability for Thirsty and Not Thirsty Rats

Abstract: The study reported four experiments aiming to test the effects of the pre-exposure schedule and water deprivation on the generalization of a conditioned taste aversion in rats, with a particular focus on testing whether or not the concurrent schedule might enhance generalization. In two experiments, non-water-deprived rats received concurrent, intermixed, or blocked exposure to a sweet-acid solution and a salty-acid solution before conditioning of one of these compounds and testing of both flavors. During pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…Using this approach, we found that after a single conditioning trial, animals can form a long-lasting generalized aversion that persists up to 2 weeks post-CTA training. This persistence, to our knowledge, is longer than any reported thus far in the CTA literature on generalization ( Domjan, 1975 ; Parker and Revusky, 1982 ; Richardson et al, 1984 ; Smith and Theodore, 1984 ; Frank and Nowlis, 1989 ; Chotro and Alonso, 1999 ; Heyer et al, 2003 ; Baird et al, 2005 ; Smith et al, 2012 ; Angulo, 2018 ). The ethological significance of this behavior and the mechanism by which this generalization is occurring remain to be worked out.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Using this approach, we found that after a single conditioning trial, animals can form a long-lasting generalized aversion that persists up to 2 weeks post-CTA training. This persistence, to our knowledge, is longer than any reported thus far in the CTA literature on generalization ( Domjan, 1975 ; Parker and Revusky, 1982 ; Richardson et al, 1984 ; Smith and Theodore, 1984 ; Frank and Nowlis, 1989 ; Chotro and Alonso, 1999 ; Heyer et al, 2003 ; Baird et al, 2005 ; Smith et al, 2012 ; Angulo, 2018 ). The ethological significance of this behavior and the mechanism by which this generalization is occurring remain to be worked out.…”
Section: Discussionmentioning
confidence: 52%
“…This feature of CTA learning makes it an ideal paradigm to explore how differences in conditioning strength might alter the temporal dynamics of memory generalization. The generalized aversion resulting from CTA conditioning is a well-documented phenomenon ( Domjan, 1975 ; Parker and Revusky, 1982 ; Richardson et al, 1984 ; Smith and Theodore, 1984 ; Frank and Nowlis, 1989 ; Chotro and Alonso, 1999 ; Heyer et al, 2003 ; Baird et al, 2005 ; Smith et al, 2012 ; Angulo, 2018 ; Wu et al, 2021 ), but it is unclear how long this generalization can persist, which factors impact its duration, and the cellular basis of this persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, we found that after a single conditioning trial, animals can form a long-lasting generalized aversion that persists up to two weeks post-CTA training. This persistence, to our knowledge, is longer than any reported thus far in the CTA literature on generalization (Domjan, 1975;Parker & Revusky, 1982;Richardson, Williams, & Riccio, 1984;Smith & Theodore, 1984;Frank & Nowlis, 1989;Chotro & Alonso, 1999;Heyer et al, 2003;Baird, St. John, & Nguyen, 2005;Smith et al, 2012;Angulo, 2018). The ethological significance of this behavior and the mechanism by which this generalization is occurring remain to be worked out.…”
Section: Discussionmentioning
confidence: 66%
“…This feature of CTA learning makes it an ideal paradigm to explore how differences in conditioning strength might alter the temporal dynamics of memory generalization. The generalized aversion resulting from CTA conditioning is a well-documented phenomenon (Domjan, 1975; Parker & Revusky, 1982; Richardson, Williams, & Riccio, 1984; Smith & Theodore, 1984; Frank & Nowlis, 1989; Chotro & Alonso, 1999; Heyer et al, 2003; Baird, St. John, & Nguyen, 2005; Smith et al, 2012; Angulo, 2018; Wu, Ramos, et al, 2021), but it is unclear how long this generalization can persist, which factors impact its duration, and the cellular basis of this persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, a diferencia de lo encontrado en humanos, la generalización de una respuesta condicionada entre estímulos similares en ratas parece ser mayor tras una preexposición concurrente que alterna o en bloques (e.g, Alonso & Hall, 1999;Rodríguez & Alonso, 2008;Rodríguez, Blair, & Hall, 2008;véase también Bennett & Mackintosh, 1999;Honey & Bateson, 1996) o al menos, no menor (e.g, Angulo, 2018). En tanto que el grado de generalización entre estímulos y su diferenciación guardarían entre sí una relación inversamente proporcional (a menor diferenciación, mayor generalización), estos resultados estarían indicando justo lo contrario a lo observado en humanos: una menor diferenciación de los estímulos después de una preexposición concurrente que alterna o en bloques.…”
unclassified